Diversity and safety on campus @ Western: Heterosexism and cissexism in higher education. Issue 3 (September 2019) - Asquith, Nicole L.; Ferfolia, Tania; Brady, Brooke; Hanckel, Benjamin
Discrimination, harassment and violence can vitiate staff and students' experiences of education and work. Although there is increasing knowledge about these experiences in primary and secondary education, very little is known about them in higher education. This paper draws from landmark research that examines the interpersonal, educational and socio-cultural perspectives that prevail about sexuality and gender diversity on an Australian university campus. In this paper we focus on three aspects of the broader research findings: the heterosexism and cissexism experienced by sexuality and gender diverse students and staff at the university; their actions and responses to these experiences; and the impact of these experiences on victims. The research demonstrates that although the university is generally safe, sexuality and gender diverse students and staff experience heterosexist and cissexist discrimination, which can have negative ramifications on their workplace and learning experiences.